KADAR TOTAL ALKALOID, FENOLAT, DAN FLAVONOID DARI EKSTRAK ETIL ASETAT HERBA SURUHAN (Peperomia pellucida [L] Kunth) - Islamudin Ahmad; Maryono Maryono; Abdul Mun'im (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
The study aimed to determine the total alkaloid, phenolic, and flavonoid content of ethyl acetate extract of Peperomia pellucida (L.) Kunth herbs, especially the herb was obtained from oil palm plantations in Baras, Nort Mamuju District, West Sulawesi Province. The sample was macerated using n-hexane then was followed with ethyl acetate. Determination of total phenolic content was performed using Folin-Ciocalteu reagent, and its absorbance was measured at 750 nm wavelength with gallic acid as a standard. Determination of total flavonoid content was conducted using AlCl3 reagent, and the absorbance was calculated at 415 nm wavelength using quercetin as a standard. Determination of total alkaloid content was calculated against the equal piperine at a wavelength of 435 nm using Dragendorff reagent. Based on the results of determination on ethyl acetate extract of Suruhan herbs was obtained the total phenolic content of 178.768+10.63139 mg/gram, total flavonoid content of 1.397+0.004509 mg/gram, and total alkaloid content of 0.615+0.155885 mg/gram. These results are preliminary data of further studies to the isolation of the targeted compounds and the utilization purposes as a raw material of herbal medicine.